Prevalence and Correlates of Diabetic Retinopathy in a Population-based Survey of Older People in Nakuru, Kenya. (June 2014) - Mathenge, Wanjiku; Bastawrous, Andrew; Peto, Tunde; Leung, Irene; Yorston, David; Foster, Allen; Kuper, Hannah
Abstract Purpose: To estimate the prevalence of and factors associated with diabetic retinopathy (DR) among people aged ≥50 years in Nakuru, Kenya. Methods: Probability-proportional-to-size sampling was used to select 100 clusters of 50 people aged ≥50 years during 2007–2008. Households within clusters were selected through compact segment sampling. Participants underwent dilated slit lamp biomicroscopy (SLB) by an ophthalmologist and digital retinal photography. Images were graded for DR at the Moorfields Eye Hospital Reading Centre, UK. Diagnosis of DR was based on retinal images where available, otherwise on SLB. Anthropometric measures, including random glucose, and lifestyle factors were measured. Results: We examined 4414 adults (response rate 88.1%), of whom 287 had diabetes. A total of 277 of these were screened for DR by SLB, and 195 also underwent retinal photography. The prevalence of any DR diagnosed by retinal images among diabetics was 35.9% (95% confidence interval, CI, 29.7–42.6%). The most common grade of DR was mild/moderate non-proliferative DR (NPDR; 22.1%, 95% CI 16.1–29.4%), while severe NPDR and proliferative DR were less frequent (13.9%, 95% CI 10.0–18.8%). SLB significantly underdiagnosed DR compared to retinal photography, particularly for milder grades. Of 87 individuals with DR, 23 had visual impairment (visual acuity <6/12). DR was associated with younger age, male sex, duration and control of diabetes, and treatment compliance. Coverage of photocoagulation in those needing immediate laser was low (25%). Conclusion: DR remains a threat to sight in people with diabetes in this elderly Kenyan population. Screening diabetics may enable those requiring treatment to be identified in time to preserve their sight.